2016
DOI: 10.1002/jbm.a.35899
|View full text |Cite
|
Sign up to set email alerts
|

PEG‐fibrinogen hydrogels for three‐dimensional breast cancer cell culture

Abstract: Tissue-engineered three-dimensional (3D) cancer models employing biomimetic hydrogels as cellular scaffolds provide contextual in vitro recapitulation of the native tumor microenvironment, thereby improving their relevance for use in cancer research. This study reports the use of poly(ethylene glycol)-fibrinogen (PF) as a suitable biosynthetic hydrogel for the 3D culture of three breast cancer cell lines: MCF7, SK-BR-3, and MDA-MB-231. Modification of the matrix characteristics of PF hydrogels was achieved by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(84 citation statements)
references
References 61 publications
1
83
0
Order By: Relevance
“…Many groups have developed biomaterial cell culture platforms and suggested that future applications could include drug screening. [4][5][46][47] These materials could have significant impact on improving the data obtained by in vitro cell studies, if adapted to current high-throughput screening technologies. Towards this goal, we adapted our lab's existing biomaterial technologies to 96-well plates and semi-automated liquid handling robotics.…”
Section: Discussionmentioning
confidence: 99%
“…Many groups have developed biomaterial cell culture platforms and suggested that future applications could include drug screening. [4][5][46][47] These materials could have significant impact on improving the data obtained by in vitro cell studies, if adapted to current high-throughput screening technologies. Towards this goal, we adapted our lab's existing biomaterial technologies to 96-well plates and semi-automated liquid handling robotics.…”
Section: Discussionmentioning
confidence: 99%
“…[9,72] However, MDA-MB-231 breast cancer cells, which are noted for their aggressive, invasive phenotype, did not cluster in the gels but rather showed a more disordered, spread morphology, with protrusions into the surrounding matrix. [71] Collectively, these results suggest that the engineered PEG-fibrinogen platform is a suitable surrogate for Matrigel in breast cancer studies. Building on this work, a subsequent study used the PEG-fibrinogen platform to produce MCF-7 breast cancer cell spheroids via microsphere encapsulation in the hydrogels.…”
Section: Breast Cancermentioning
confidence: 90%
“…As one example, Pradhan et al utilized fibrinogen-conjugated PEG diacrylate crosslinked via a radicalinitiated chain polymerization to encapsulate breast cancer cells. [71] They adjusted the stiffness of the gels from 3.2 ± 0.5 kPa to 5.4 ± 0.5 kPa to 9.0 ± 1.4 kPa (Young's modulus) by introducing increasing concentrations of PEG diacrylate that was not fibrinogen-conjugated to the gel and observed that two breast cancer cell lines, MCF-7 and SK-BR-3, formed cell clusters after 15 days of culture and had comparable morphologies across gels of differing stiffness. These cells formed orderly spherical cell clusters, similar to the acini-like structures observed in Matrigel.…”
Section: Breast Cancermentioning
confidence: 99%
“…PEG-fibrinogen precursors were used to synthesize microspheres of adjustable stiffness and porosity for 3D culture of breast cancer cells MCF-7, SK-BR-3, and MDA-MB-231. [111] Cancer cells pre-mixed with the PEG-fibrinogen polymer precursor were suspended on a polydimethylsiloxane substrate and photo-crosslinked to form cancer cell-containing hydrogel microspheres. Hydrogels degraded over time and cells proliferated.…”
Section: 2 Synthetic Materialsmentioning
confidence: 99%